Disputes in everyday life social and moral orders of children and young people - Danby, Susan; Theobald, Maryanne (Emerald, 2012)
Volume 15 of Sociological Studies of Children and Youth investigates the interactional procedures used by children and young people as disputes arise in varying contexts of their everyday life. Disputes are a topic of angst and anxiety for children, young people and adults alike, and yet are important times for interactional matters to be addressed. A particular intention of the book is its ethnomethodological focus, bringing a fine-grained analysis and understanding to disputes and related interactional matters. Such analysis highlights the in situ competency of children and young people as they manage their social relationships and disputes to offer insight into how children arrange their social lives within the context of school, home, neighbourhood, correctional, club and after school settings. This volume offers a contemporary understanding of the relational matters of childrens peer cultures to better understand and address the complex nature of children and young peoples everyday lives in todays society. Papers include: when verbal disputes get physical; conditional threats in young childrens peer interaction; and young childrens disputes during computer game playing.
Keywords: Social Science -- Sociology -- General.; Social Science -- Children's Studies.; Social Science -- General.; Sociology.; Social issues (Children's/YA).; Child development.; Interpersonal conflict in children.; elektronické knihy; electronic books